Influence of Dietary Chromium and Vitamin E Supplementation on Performance, Metabolism, and Physiology of Broilers Subjected to Cyclic Heat Stress - ML X Júnior; RD Bernardes; CH Oliveira; KMM Dias; BF Almeida; SO Borges; FS Dalólio; KM Gomes; CJ Rodrigues; AA Calderano (Brazilian Journal of Poultry Science)
ABSTRACT This experiment evaluated the influence of chromium (Cr) and vitamin E (VitE) supplementation on the performance, glucose levels, thyroid hormone levels, immune and oxidative response, and 70 kilodalton heat shock protein (HSP70) mRNA expression of broilers under heat stress (HS). Male chickens (n = 768, 22 days old) were randomly assigned to a 4x3 factorial with 4 Cr levels (0, 500, 1000, and 1500 ppb) and 3 VitE levels (0, 150, and 300 mg/kg), totaling 12 treatments with 8 replicates and 8 birds per experimental unit. Performance, glucose levels, thyroid hormone levels, heterophil-to-lymphocyte (H:L) ratio, malondialdehyde (MDA) in muscle, relative weight of lymphoid organs, and HSP70 mRNA expression were measured. VitE at 150 mg/kg improved FI and BWG (p ≤ 0.05). The combination of Cr 1500 ppb and VitE 150 mg/kg reduced FCR (p ≤ 0.05). Cr and VitE had single effects on glucose levels (p ≤ 0.05) and their interaction influenced thyroid hormone levels (p ≤ 0.05). Cr 1500 ppb with VitE 300 mg/kg lowered the H:L ratio and HSP70 mRNA expression (p ≤ 0.05). VitE at 300 mg/kg increased spleen relative weight (p ≤ 0.05). Cr supplementation reduced MDA concentrations (p ≤ 0.05). In conclusion, Cr and VitE, individually or combined, benefitted performance, glucose and thyroid hormone levels, immune and oxidative response, and heat stress tolerance.